Enhancing Focus and Concentration: Implementing Vocabulary Repetition in Arabic Language Learning - Rahma, Dewi; Basit, Abdul (Program Pascasarjana Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
In a learning context, focus and concentration are important factors in the success of learning the Arabic language. The repetition method is one of the methods used to improve memory and understanding of vocabulary (mufrodat). This research aims to test the effectiveness of applying the vocabulary repetition method to enhance students' focus and concentration in Arabic language learning. The research uses a qualitative approach, which analyzes how vocabulary repetition can strengthen students' memory, facilitate understanding, and enhance participation and motivation in learning. The research results show that the vocabulary repetition method helps students remember for a more extended period and also improves their concentration during the learning process. Thus, this vocabulary repetition method can be an effective strategy to maximize students' focus and concentration in learning Arabic